Odpowiedzi

2009-09-21T21:12:16+02:00
1) K2O + H2SO4 ----> K2SO4 + H2O
2) CaO + 2HNO3 -----> Ca(NO3)2 + H2O
3) 2Al(OH)3 + 3H2SO4 -----> Al2(SO4)3 + 6H2O
4)Mg(OH)2 + H2CO3 -----> MgCO3 + 2H2O
5)Al2O3 + 6HCl------> 2AlCl3 + 3H2O
6) MgO + H2S -----> MgS + H2O
11 4 11
  • Użytkownik Zadane
2009-09-21T21:52:31+02:00
1) K₂O + H₂SO4 → K₂SO₄ + H₂O
2) CaO + 2HNO₃ → Ca(NO₃)₂ + H₂O
3) 2Al(OH)₃ + 3H₂SO₄ → Al₂(SO₄)₃ + 6H₂O
4) Mg(OH)₂ + H₂CO₃ → MgCO₃ + 2H₂O
5) Al₂O₃ + 6HCl → 2AlCl₃ + 3H₂O
6) MgO + H₂S → MgS + H₂O
2 5 2